Effectiveness of family interventions on psychological distress and expressed emotion in family members of individuals diagnosed with first-episode psychosis: A systematic review - Wilai Napa (2018)
© 2017 THE JOANNA BRIGGS INSTITUTE. Background Acritical period for persons with first-episode psychosis is the first two years after diagnosis, when they are at high risk of suicide attempts, violent behaviors and substance abuse. This period also has a great impact on the psychological distress of family members, particularly caregivers who either provide care or live with ill family members. In addition, the families also report feelings of being overwhelmed when accessing service facilities at this critical point. These consequences impact on the affective tone/atmosphere in the family, also referred to as so-called expressedemotion. In addition, expressed emotion research has indicated that the family atmosphere contributes to recurrent psychosis and lengthy hospital stays for patients in the initial phase.1,44-45 Therefore, family interventions aimed at reducing psychological distress and improving expressed emotion in families during this critical time are very important. Modern research has yielded international evidence addressing these outcomes, but little is known about which interventions are the most effective. Therefore, this review aimed to evaluate the effectiveness of these interventions. Objectives The objective of this review was to examine the effectiveness of family interventions on psychological distress and expressed emotion in family members of persons with first-episode psychosis (FEP). Inclusion criteria Types of participants Family members of persons with FEP and who had received treatment after being diagnosed within two years. Types of intervention(s) Studies that examined interventions among family members of persons with FEP. Family interventions referred to any education, psychoeducation, communication, coping and problem-solving skills training and cognitive behavioral therapy that was provided to family members of persons with FEP. Outcomes Psychological distress and expressed emotions of those family members. Types of studies Randomized controlled trials, quasi-experimental studies, cohort studies and case-control studies. Search strategy The preliminary search was conducted in MEDLINE and CINAHL with keywords containing the title, abstract and subject description analysis as the first identification of related studies. An extensive search was conducted in other databases including ProQuest Dissertations and Theses, ScienceDirect, Scopus, PsychINFO, ThaiLIS and Thai National research databases. In addition, searches of reference lists and other manual searches were undertaken. Methodological quality Studies were critically appraised by two independent reviewers for methodological validity prior to inclusion in the review using standardized critical appraisal instruments from the Joanna Briggs Institute. Data extraction Data were extracted using the standardized data extraction tools from the Joanna Briggs Institute. The mean score and standard deviation (SD) were extracted for targets outcomes relating to psychological distress and expressed emotion. Data synthesis Quantitative data could not be pooled due to the heterogeneity of the included studies. Data were synthesized based on the individual results from the three included studies and have been presented in a narrative format accompanied with tabulated data. Results Data synthesis of the three individual studies indicated that there were no statistically significant interventions that address psychological distress and expressed emotion in family members who live with and care for persons with FEP. There is insufficient evidence available to evaluate the effect sizes for pooled outcomes. Conclusion Based on the results of this review, there is insufficient evidence to validate the effectiveness of family interventions on psychological distress and expressed emotion in family members who live with and care for persons with FEP. In addition, based on the individual primary studies, the implications for practice should be carefully considered.